2017
DOI: 10.1016/j.aca.2016.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-flow paper SERS system for therapeutic drug monitoring of flucytosine in serum

Abstract: A number of life-saving drugs require therapeutic drug monitoring (TDM) for safe and effective use. Currently, however, TDM is performed using sophisticated analytical techniques relegated to central labs, increasing the cost per test and time to answer. Here, using a novel vertical flow membrane system with inkjet-printed surface enhanced Raman sensors, along with a portable spectrometer, we demonstrate a low cost and easy to use device to quantify levels of flucytosine, an antifungal that requires TDM for ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 49 publications
(83 reference statements)
0
59
0
1
Order By: Relevance
“…Finally, precision medicine also involves trends in grouping patients into different subtypes in order to more accurately monitor their individual responses to drugs. A vertical-flow paper-based POC assay was developed to be used with a low-cost, bench-top fluorometer for monitoring therapeutic response via surface enhanced Raman detection 113 . The device operated on undiluted serum and provided a result in under 15 minutes 113 .…”
Section: Recent Developments In Poc Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, precision medicine also involves trends in grouping patients into different subtypes in order to more accurately monitor their individual responses to drugs. A vertical-flow paper-based POC assay was developed to be used with a low-cost, bench-top fluorometer for monitoring therapeutic response via surface enhanced Raman detection 113 . The device operated on undiluted serum and provided a result in under 15 minutes 113 .…”
Section: Recent Developments In Poc Diagnosticsmentioning
confidence: 99%
“…A vertical-flow paper-based POC assay was developed to be used with a low-cost, bench-top fluorometer for monitoring therapeutic response via surface enhanced Raman detection 113 . The device operated on undiluted serum and provided a result in under 15 minutes 113 . Such near-patient devices hold potential in implementing precision medicine across a broad range of clinical settings.…”
Section: Recent Developments In Poc Diagnosticsmentioning
confidence: 99%
“…On the basis of excellent liquid conductivity and softness, various detection modes have been proposed, such as wiping type, lateral flow, and longitudinal flow . For instance, White et al proposed a low cost and easy device using a novel vertical flow membrance system with inkjet‐printed technique . Tian et al demonstrated a novel SERS substrate based on common filter paper together with Au nanorods, which allows conformal contact with real‐world surfaces, resulting in highly enhancing the sample collection efficiency compared with conventional substrates .…”
Section: Introductionmentioning
confidence: 99%
“…So far, this effect, called surface enhanced Raman scattering (SERS), has been widely explored for the analysis of biological samples for different purposes, i.e. classification of different bacterial species [37], gene expression estimation [38] and detection of drugs [3940]. Unfortunately, these studies are limited to the analysis of few biomolecules.…”
Section: Introductionmentioning
confidence: 99%